2012
DOI: 10.1007/s12052-012-0446-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Apartheid: On the Manner in Which High School Students Understand Evolution without Believing in Evolution

Abstract: High school science students are often unwilling to learn about evolution due to a perceived conflict with their religious beliefs. Other students are able to understand evolution despite the fact that they do not believe in evolution. According to Cobern (Sci Educ 80:579-610, 1996), students can wall off that which is believed from that which is not believed in a process he called cognitive apartheid. A mixed-methods study was conducted to determine the extent to which understanding of evolution differed amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 26 publications
2
42
0
1
Order By: Relevance
“…One study found that being able to explain these concepts is uncorrelated with accepting them as true (Shtulman 2006). In other words, learning the content of evolutionary theory does not automatically lead to a belief that it is accurate and REJECTING EVOLUTION 577 true in the same way that someone might come to "believe" in photosynthesis after learning about how plants convert light into chemical energy (Hermann 2012).…”
Section: Two Models Of Cognitionmentioning
confidence: 99%
“…One study found that being able to explain these concepts is uncorrelated with accepting them as true (Shtulman 2006). In other words, learning the content of evolutionary theory does not automatically lead to a belief that it is accurate and REJECTING EVOLUTION 577 true in the same way that someone might come to "believe" in photosynthesis after learning about how plants convert light into chemical energy (Hermann 2012).…”
Section: Two Models Of Cognitionmentioning
confidence: 99%
“…Misunderstandings of natural selection and other evolutionary mechanisms are not necessarily related to the pervasive resistance to the idea of evolutionary origins, especially of humans (Evans et al 2010;Hermann 2012;Kahan 2015). Inconsistent use of terms-such as acceptance, belief, understanding, and knowledge-and difficulties measuring those constructs, has made it challenging to achieve consensus on the nature of the relationship between understanding and acceptance (Smith 2009;Southerland et al 2001).…”
Section: Belief Understanding Acceptance and Knowledgementioning
confidence: 99%
“…One study found that being able to explain these concepts is uncorrelated with accepting them as true (Shtulman ). In other words, learning the content of evolutionary theory does not automatically lead to a belief that it is accurate and true in the same way that someone might come to “believe” in photosynthesis after learning about how plants convert light into chemical energy (Hermann ).…”
Section: Two Models Of Cognitionmentioning
confidence: 99%